Avian Pigment Pattern Formation: Developmental Control of Macro- (Across the Body) and Micro- (Within a Feather) Level of Pigment Patterns - Inaba, Masafumi; Chuong, Cheng-Ming (Frontiers in Cell and Developmental Biology, 2020)
Animal color patterns are of interest to many fields, such as developmental biology, evolutionary biology, ethology, mathematical biology, bio-mimetics, etc. The skin provides easy access to experimentation and analysis enabling the developmental pigment patterning process to be analyzed at the cellular and molecular level. Studies in animals with distinct pigment patterns (such as zebrafish, horse, feline, etc.) have revealed some genetic information underlying color pattern formation. Yet, how the complex pigment patterns in diverse avian species are established remains an open question. Here we summarize recent progress. Avian plumage shows color patterns occurring at different spatial levels. The two main levels are macro- (across the body) and micro- (within a feather) pigment patterns. At the cellular level, colors are mainly produced by melanocytes generating eumelanin (black) and pheomelanin (yellow, orange). These melanin-based patterns are regulated by melanocyte migration, differentiation, cell death, and/or interaction with neighboring skin cells. In addition, non-melanin chemical pigments and structural colors add more colors to the available palette in different cell types or skin regions. We discuss classic and recent tissue transplantation experiments that explore the avian pigment patterning process and some potential molecular mechanisms. We find color patterns can be controlled autonomously by melanocytes but also non-autonomously by dermal cells. Complex plumage color patterns are generated by the combination of these multi-scale patterning mechanisms. These interactions can be further modulated by environmental factors such as sex hormones, which generate striking sexual dimorphic colors in avian integuments and can also be influenced by seasons and aging.